Nanopore sequencing of clonal IGH rearrangements in cell-free DNA as a biomarker for acute lymphoblastic leukemia - Sampathi, Shilpa; Chernyavskaya, Yelena; Haney, Meghan G.; Moore, L. Henry; Snyder, Isabel A.; Cox, Anna H.; Fuller, Brittany L.; Taylor, Tamara J.; Yan, Donglin; Badgett, Tom C.; Blackburn, Jessica S. (Frontiers in Oncology, 2022)
Acute Lymphoblastic Leukemia (ALL) is the most common pediatric cancer, and patient with relapsed ALL have a poor prognosis. Detection of ALL blasts remaining at the end of treatment, or minimal residual disease (MRD), and spread of ALL into the central nervous system (CNS) have prognostic importance in ALL. Current methods to detect MRD and CNS disease in ALL rely on the presence of ALL blasts in patient samples. Cell-free DNA, or small fragments of DNA released by cancer cells into patient biofluids, has emerged as a robust and sensitive biomarker to assess cancer burden, although cfDNA analysis has not previously been applied to ALL. This study describes a novel method for detecting the presence of cell-free DNA in ALL patients' blood and cerebrospinal fluid using Nanopore sequencing. This method is a simple and rapid workflow that can detect clonal heterogeneity by analyzing B cell-specific rearrangement of the (IGH) locus in cfDNA from B-ALL patient samples. Quantitation of IGH-variable sequences in cfDNA allowed us to track the response of individual B-ALL clones throughout treatment. The detection of cfDNA in patient biofluids aligned with clinical diagnoses of MRD and CNS disease in the patient cohort, and leukemic clones could be detected even when diagnostic cell-count thresholds for MRD were not met. These data suggest that cfDNA assays may be useful in detecting the presence of ALL in the patient, even when blasts are not physically present in the biofluid sample. The Nanopore IGH detection workflow to monitor cell-free DNA is a simple, rapid, and inexpensive assay that may ultimately serve as a valuable complement to traditional clinical diagnostic approaches for ALL.